Формування іміджу авторитарного лідера в сучасних умовах - Шурко, О.; Новик, А. (Видавництво Львівської політехніки, 2010)
Висвітлено запити та потреби суспільства в сильному лідері авторитарного типу. Розглянута різниця між іміджем демократичного та авторитарного лідера і їх специфіки формування. In this article "Forming the image of authoritarian leader in modern conditions" the authors are trying to present inquires and needs of society in a strong leader of authoritarian type. In the article the difference between image of democratic and the authoritarian leader and the specific of their forming is describing. The article is prescribed to the experts who are interested in practical politology, teachers and students at the department of political sciences.
Forming the image of authoritarian leader in modern conditions
Keywords: маніпулювання; політичний імідж; авторитарний; авторитетний; вождь; унікальна політична пропозиція; передвиборча політична легенда; manipulation; political image; authoritarian; authoritative; fugleman; unique political suggestion; pre-election political legend